THE INFLUENCE OF PROMOTION AND BRAND IMAGE TOWARD PURCHASE DECISION OF HONDA VARIO - Eko Putra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
The purpose of this researchis to know the influence of promotion and brand image on the decision to purchase a Honda Vario motorcycle in West Pasaman. The population insthis research were all consumers who used Honda Vario motorcycle in West Pasaman . The sampling technique used was a Non Probability Sampling sample. Research instrument is a questionnaire. The data obtained were then processed using multiple linear regression analysis using SPSS. From the results of this researchfound the promotion variables (X1), and brand image (X2) have a significant effect on purchase decision with a significant level of 0,000. The magnitude of the effect of promotion (X1), and brand image (X2) on purchasing decisions (Y) is 0.781 or equal to 78.1% Keywords: Purchase Decision, Promotion, Brand Image